Educação do campo para convivência com o semiárido potiguar: semeando possibilidades através de práticas contra-hegemônicas da licenciatura interdisciplinar em educação do campo na UFERSA - Pereira, Linconly Jesus Alencar (2018)
The collective social imaginary construction of the Semiarid as a space of drought, suffering, hunger and misery was rooted in Brazilian minds and culture. This stereotype of the scourge, linked to the men and women of the Semiarid, doesn´t shape the struggle and resistance of the Northeastern populations, does not figure out their culture, knowledge, traditions, knowledge. That is part of the Semiarid reality. In this context, this research begins with our teaching practice in the Education College of the Central Ufersa campus, located in Mossoró-RN. We draw as a general objective of this work, to analyze the contributions of Ledoc to the promotion of a social, popular counter-hegemonic project that strengthens Family Agriculture based on educational practices for coexistence with the the Semiarid. We take a look in Apodi Village as an investigation subject, as we understand from the speech of the research subjects/students of Ledoc, the strategies of struggle and resistance of the family farmers against the intensive expansion of agribusiness of the irrigated fruit region and the struggle of peasant social movements. We used as a structuring element the theoretical approach of the historical-dialectical materialism method, but also made use of field diaries and semistructured interviews as elements of data collection. This scenario allowed us to develop this qualitative research in two research moments, being the first in the school/university time and the second in community time, enabling us to understand, reflect, experience and investigate the strategies of coexistence with the semiarid developed in the territory of Chapada do Apodi. We propose, based in our thesis conclusion that the Field Education developed by Ledoc made it possible Apodi Village understood a hegemonic social project to strengthen Family Agriculture through educational practices for the coexistence with the Semiarid based on the Popular Education and the Education of the Country.